Learning Parallel Computing Concepts via a Turing Machine Simulator - Py, Mônica Xavier; Toscani, Laira Vieira; Lamb, Luís C.; Diverio, Tiarajú Asmuz (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance Computing, 2001)
lt is well-known that technology developments in Computing Science has led to new developments in Computing Theory and vice-versa. This work is a contribution towards the formalisation of Parallel Processing concepts. We exploit variations of the Turing Machine model, referred as natural extensions, which may be composed by several control units, tapes and heads in such a way that one can define a variety of Parallel Turing Machine models. Several notions and definitions of parallelism are identified including computability, complexity and performance of computations. A prototype of the Parallel Turing Machine model is presented. This prototype was used as a test bed for the assessment of the usefulness of these machine models as a parallel processing teaching tool, as well as a tool to facilitate the creation of a "culture" among students in high performance computing. Finally, we analyse the notions of performance, speedup, efficiency, load balancing, synchronisation and communication in parallel processing.